Respuesta :

Answer:

a = (p - b)/2

Step-by-step explanation:

Isolate the variable, a. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

PEMDAS is the order of operation, and  =

Parenthesis

Exponents (& roots)

Multiplication

Division

Addition

Subtraction

~

First, subtract b from both sides:

p (-b) = 2a + b (-b)

p - b = 2a

2a = p - b

Next, divide 2 from both sides:

(2a)/2 = (p - b)/2

a = (p - b)/2

a = (p - b)/2 is your answer.

~

Answer:

a = (p + b) / 2

Step-by-step explanation:

p = 2a + b

2a - b = p

+b

2a = p + b

/ 2

a = p + b

a = (p + b) / 2